The impact of natural and human factors on the spread of deaths in Yemen during the era of The Rasulid state (626-858 AH) - Al-Mohammadi, Samira Saud (Journal of Humanities & Social Sciences, 2024)
Studying the social aspect is one of the important aspects of Islamic civilization, as it sheds light on people’s lives in their finest details and the extent to which they are affected by other aspects such as political, economic, and scientific. We have discussed in this study the effect of natural and human factors on the spread of deaths in Yemen during the era of the Rasulid state.